The effectiveness of non-attendance triage training based on the ESI-IV system on the knowledge and ability of pre-hospital emergency staff in the academic hospitals of Ahvaz Jundishapur university of medical sciences - Ali Vefagh Nematollahi; Mofid Hosseinzadeh; Alireza Rafati Navaei; Payam Amini; Maryam Asiaban (Journal of Preventive Epidemiology)
Introduction: In recent decades, E-learning has gained widespread recognition globally as a vital application of information and communication technology. Objectives: The present study investigated the effectiveness of non-attendance triage training based on the ESI-IV system on the knowledge and ability of pre-hospital emergency staff. Patients and Methods: This study was a semi-experimental interventional study, and the study population consisted of the pre-hospital emergency staff of Ahvaz university of medical sciences academic hospitals in 2021. The study tool was a questionnaire on the awareness and performance of the triage system of hospital emergency (ESI). Initially, both questionnaires were completed, and submitted the triage training file to the intervention group. Two weeks after the first phase—completion of the questionnaire for the first time— and the study of the file by the subjects, the questionnaire was completed again by the intervention group, and the data of both groups were compared. Results: According to the results, the mean of awareness and decision-making in the control group before and after the intervention was (11.8, 10.85, and 13.82) and (7.51, 7.36, and 8.86) respectively. The results indicate that non-attendance triage training based on the ESI-IV system was effective in the knowledge and ability of the pre-hospital emergency personnel had a positive and significant impact, and remains at a good level. Conclusion: The present results of the research indicate that the use of non-attendance training as an effective method can improve interns’ knowledge and ability.